Synthesis and structural studies of 2-[3-(4-methoxybenzoyl) thioureido]phenyl propionic acid and 2-[3-(4-methoxybenzoyl) thioureido]-3-(1H-indole-3-yl) propionic acid - Ngah, Nurziana; M Yamin, Bohari; Kassim, Mohammad (2010)
Two 4-methoxybenzoylthiourea of propionic acid namely 2-[3-(4- Two 4-methoxybenzoylthiourea of propionic acid namely 2-[3-(4-methoxybenzoyl)thioureido]phenylpropionic acid (I) and 2-[3-(4-methoxybenzoyl) thioureido]-3-(1H-indole-3-yl)propionic acid (II) have been successfully synthesized. The compounds were analyzed and characterized by elemental analysis, infrared spectroscopy and X-ray crystallography. Both compounds crystallized in orthorhombic crystal system with space group P21 21 21, a = 5.0364(13) Å, b = 16.716(4) Å, c = 23.040(6) Å and Z = 4 and Pbcn, a = 18.247(4) Å, b = 14.083(3) Å, c = 14.736(3) Å and Z = 8, respectively. As in most carbonoylthiourea compounds, the molecules adopts trans-cis configuration with respect to the position of 4-methoxybenzoyl and the propionic acid moieties against the thiono S atom across their C-N bonds. Molecule (I) is associated with one methanol molecule as molecule of recrystalization.